PENGARUH KEMAMPUAN DAN LINGKUNGAN TERHADAP KINERJA PEGAWAI PADA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN MUSI RAWAS - Suyadi Suyadi (Imara: JURNAL RISET EKONOMI ISLAM, 2018)
This study aims to determine the ability and work environment on the performance of employees at the Regional Disaster Management Board of Musi Rawas Regency. The population was 54 employees. Data were collected through questionnaires, and analyzed by using simple linear test, correlation coefficient, t test, multiple regression, determination coefficient, and F test. The research findings reflected couple things. First, there is a significant influence of the employees’ ability towards their performance partially in Regional Disaster Management Board of Musi Rawas Regency. It is supported by the simple partial regression test results is equal to 27.903. Testing Hypothesis Test is 2,957 ≥ t table 1,673. Second, there is a significant influence of the employees’ work environment towards their performance partially in Regional Disaster Management Board of Musi Rawas Regency. It is proofed by simple partial regression test results is equal to 0.556. Testing Hypothesis Test is 2,957 ≥ t table 1,673. Third, there are significance influence of both the employees’ ability and work environment towards their performance all together in Regional Disaster Management Board of Musi Rawas Regency. It is explained through hypothesis Test Testing with F test obtains F count value of 42.721 and the level of significance simultaneously sig F is 0.000 α α (0.05).